The Influence of Clo3D Software on Sustainable Fashion Practices: A Comprehensive Literature Analysis - Khomariah, Sinta; Febriana, Rina; Gede Putri, Vera Utami (Mutiara Intelektual Indonesia Press, 2025)
The fashion industry is increasingly turning to digitalization to address the pressing challenges of sustainability. This comprehensive literature analysis explores the influence of Clo3D software on sustainable fashion practices, focusing on its environmental, social, and economic impacts. Clo3D, a 3D garment visualization tool, has been adopted by designers and manufacturers to reduce waste, improve design efficiency, and enhance resource management. A systematic literature review examined studies highlighting the application of Clo3D in sustainable fashion initiatives. The results reveal that Clo3D significantly contributes to environmental sustainability by reducing fabric waste and enabling more precise production processes. Additionally, the software promotes social sustainability by fostering inclusivity and transparency in design and production workflows. From an economic standpoint, Clo3D aids in reducing costs and accelerating time-to-market for sustainable fashion products. However, challenges such as accessibility and the learning curve for new users remain barriers to its widespread adoption. This review underscores the transformative potential of digital tools like Clo3D in advancing sustainability within the fashion industry. It suggests avenues for future research to explore the integration of digital technologies in sustainable fashion practices further